From chorismos to epekeina tes ousias: mathematics and hermeneutics in Plato’s philosophy - Alberto Guido Giovanni Zali (Plato, 2025)
This paper proposes a reading of Plato’s Republic and Theaetetus, so as to analyze the three levels of transcendence in which experience unfolds. First, it is necessary to overcome the doxastic plane: therein an ens may be and not be within an equal respect, generating a contradiction which removable via hypothesises. Still, hypothesises produce an indefinite regression: a hermeneutic step towards Forms is hence needed. The alogon is interpreted as the transcendent and luminous source of every subsequent discourse. Ultimately, the case of the epekeina tes ousias shows transcendence to depend on a hermeneutic activity aimed at saving the phenomena.